2019
DOI: 10.1038/s41467-019-08927-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for assembly of vertical single β-barrel viruses

Abstract: The vertical double β-barrel major capsid protein (MCP) fold, fingerprint of the PRD1-adeno viral lineage, is widespread in many viruses infecting organisms across the three domains of life. The discovery of PRD1-like viruses with two MCPs challenged the known assembly principles. Here, we present the cryo-electron microscopy (cryo-EM) structures of the archaeal, halophilic, internal membrane-containing Haloarcula californiae icosahedral virus 1 (HCIV-1) and Haloarcula hispanica icosahedral virus 2 (HHIV-2) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…D) and protein quantities (Table ), but the purified particles had specific infectivity of ~2 × 10 9 pfu/mg of protein (Table ), which is 3–4 magnitudes lower than e.g. the specific infectivities of the purified virus samples of haloarchaeal tailed virus HSTV‐1 (~9 × 10 12 pfu/mg of protein) and icosahedral membrane‐containing virus HCIV‐1 (~1 × 10 12 pfu/mg of protein), of which have been analysed structurally (Pietilä et al ., ; Demina et al ., ; Santos‐Perez et al ., ). The negative staining and TEM of the purified HFTV1 particles revealed that some of particles had lost their genome explaining partly the loss of infectivity (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…D) and protein quantities (Table ), but the purified particles had specific infectivity of ~2 × 10 9 pfu/mg of protein (Table ), which is 3–4 magnitudes lower than e.g. the specific infectivities of the purified virus samples of haloarchaeal tailed virus HSTV‐1 (~9 × 10 12 pfu/mg of protein) and icosahedral membrane‐containing virus HCIV‐1 (~1 × 10 12 pfu/mg of protein), of which have been analysed structurally (Pietilä et al ., ; Demina et al ., ; Santos‐Perez et al ., ). The negative staining and TEM of the purified HFTV1 particles revealed that some of particles had lost their genome explaining partly the loss of infectivity (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Juxtaposed to the p72 proteinaceous shell, the icosahedrally ordered membrane is apparent, with an overall thickness of ϳ34 Å (peak-to-peak distance in Fig. 1C) that is in line with EDITORS' PICK: Cryo-EM of African swine fever virus other membrane-containing viruses (32,38,39). Weak densities across the p72 shell and the outer leaflet of the membrane support the contact of these two architectural constituents (Fig.…”
Section: Asfv Structurementioning
confidence: 56%
“…3C) (36), and the high hydrophobicity score of the first 10 residues [relative to the first 40 assessed using ProtScale (45)] support a model in which these helices contact the underneath membrane as also seen for PRD1 MCP P3 (32). Further contacts might also occur at the 5-fold vertices between penton proteins and the apex of the inner membrane as observed in membrane-containing viruses, such as STIV and HCIV-1, which interact with the above penton (39,44). It has been proposed that the capsid assembly of CroV and related giant viruses may initiate at a 5-fold vertex to continuously proceed outward in a spiraling fashion (27), and the same pathway might be used by ASFV.…”
Section: Structure and Assembly Of The Outer Capsidmentioning
confidence: 67%
See 2 more Smart Citations